LITERASI KEUANGAN TERHADAP KINERJA BISNIS PADA UMKM MELALUI ENTREPRENEUR MINDSET - Septiannisa Paramita; Hikmayani Subur (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the influence of financial literacy on the business performance of Micro, Small, and Medium Enterprises (MSMEs), with the entrepreneur mindset as a mediating variable. Financial literacy is defined as a strategic skill in financial management, investment optimization, and business risk mitigation, while the entrepreneur mindset serves as a key driver in fostering innovation, bold decision-making, and risk adaptation. Using a qualitative research method through in-depth interviews with five MSME actors in Rappocini District, Makassar City, the study reveals that adequate financial literacy positively contributes to financial management, operational efficiency, and business growth. The entrepreneur mindset is found to strengthen the relationship between financial literacy and business performance, particularly in aspects of innovation, strategic decision-making, risk tolerance, and leadership ability. These findings highlight the importance of integrating financial literacy and entrepreneurial mindset in building resilient and competitive MSMEs in the digital era. The study also recommends the development of financial education programs and entrepreneur mindset training based on the actual needs of MSMEs as a strategy to enhance national competitiveness.